Cognitive and functional changes in prediagnostic phase of Parkinson disease: A population-based study. (October 2020) - Foubert-Samier, Alexandra; Helmer, Catherine; Le Goff, Mélanie; Guillet, Florian; Proust-Lima, Cécile; Jacqmin-Gadda, Hélène; Dartigues, Jean-François; Amieva, Hélène; Tison, François
Abstract: Introduction: Prodromal non-motor symptoms precede, often by decades, motor signs and diagnosis of Parkinson's disease. It is however still uncertain if cognitive changes belong to the spectrum of non-motor prodromal Parkinson's disease. Thanks to the very long-term follow-up of the PAQUID population-based cohort, we assessed trajectories of cognitive complaints and functioning over a 13-year period before the diagnosis of late onset Parkinson's disease. Methods: This study relies on a matched nested case-control sample selected from the cohort. Of the 3777 initial subjects of the cohort, 43 developed incident Parkinson's disease over the follow-up. The mean age at diagnosis was 78.0 (standard deviation = 5.8) years and 46.5% were men. These cases were matched to 86 elderly control subjects. Scores of different cognitive domains, daily function, and depressive symptoms were described throughout the follow-up using mixed-effects models. Results: No significant global cognitive decline preceded the diagnosis of late onset Parkinson's disease. However, psychomotor speed appeared significantly slower 2 years before the diagnosis and depressive symptoms 12 years before. Global score of instrumental activities of daily living became altered 2–3 years preceding the diagnosis of late onset Parkinson's disease, including the use of public transportation that was altered ten years before the diagnosis. Conclusion: In late onset Parkinson's disease, while global cognitive functions seem preserved, psychomotor speed starts to decline 2 years before the diagnosis and activities of daily living are also impacted. Depressive symptoms appear very early in the prediagnosic phase. Highlights: Global cognition seems preserved in the prodromal phase of PD. Depressive symptoms appear very early in the prediagnosic phase. Psychomotor speed starts to decline 2 years before the diagnosis. Psychomotor slowing could be a marker of brain vulnerability.